SUFISME DALAM SPIRITUALITAS PESMODERN - Arifin, Syamsul (Jurnal Bestari, 1994)
The appearance of Post Modern as a tendency of human new era had aroused the consciousness (awareness) and new environment in religions life. It seems that there is an eagerness to get back to the spiritual values of the religion. There is a main question, what kinds of spiritual that can fulfill human now? The writing below is trying to offer the Islamic Sufism as the alternative of spiritual reading in the future.